Factors of tourists' perspective and awareness of insects based on demographics distribution in the tropical ecosystem - Le, Gao; Saikim, Fiffy Hanisdah; M. Yusoh, Kalsum; Mohamed Dawood, Mahadimenakbar; Rahman, Homathevi; Mustaffa, Nazirah; Mohd Nordin, Nordiana; Abdul Aziz, Nor Akmar (Universiti Kebangsaan Malaysia Press, 2021)
Entomological ecotourism has developed into a modern-day definition. The promotion of entomological ecotourism makes people gaining a better understanding of insects when they participated such activity. Depending on the eco-tour context, one may learn about a particular insects’role in the ecosystem, insects’ connections with other wildlife, or the plants they depend on. Several studies reported the general preference of insects. However, there is still a lack of research for understanding the reason for similarities and differences in insects’ perceptions as a tourism product from a cultural aspect. This research aimed to study the key factors that affect tourists’ awareness and perception of insects based on their demographic profiles. The researcher used questionnaires, surveys, and interviews for data collection. The outcomes are illustrated in the form of conceptual map, quadrant report, spider-web configuration as well as tables. This cross-cultural study shows that there is little difference in perception and awareness between Malaysian and Non-Malaysian respondents. Respondents also show three main factors, such as ‘Knowledge’, ‘Experience’ and ‘Appearance’ that may cause different perceptions of insects other than their cultural background. Even though there are no significant differences between the respondents’ perceptions of insects, there are still some items among the respondents’ perceptions need to be considered. These items include the respondents’ perspective on diversity, behaviors, life cycle, and insects' appearance. Therefore, getting people to participate in entomological ecotourism, insects that fit tourists’ requirements such as beautiful, rare, and attractive, needs to be focused on. Hence, the findings are significant to share to ensure proper management of insects through entomological ecotourism or entotourism.